Social class inequalities in tooth-brushing time: The role of material, behavioral, psychosocial, and workplace environmental factors among the South Korean population - Novrinda, Herry; Han, Dong-Hun; Andreas, Peter (Makara Journal of Health Research, 2019)
Background: Inequality in health should be prevented. The aims of this study were to assess inequalities prevalent in tooth-brushing after lunch (TAL) and in tooth-brushing before sleep (TBS) among Koreans using the NMSC indicator and to assess the role of material, health behavioral, psychosocial, and workplace environmental (WPE) determinants in associating the indicator with tooth brushing activities. Methods: The data were from the 4th KNHANES with 6,710 workers and entrepreneurs from 19 to 54 year old, who were grouped into 12 social class positions. TAL and TBS were the outcomes. Data analysis was performed using a logistic regression sequence. The results were reported as OR and 95% CI. Results: The proportion of owner groups was higher for TBS than for TAL, whereas that of worker groups was higher for TAL than for TBS. The highest probability was shown by expert workers (TAL) and capitalists (TBS) among various models. WPE factors had the highest explanatory power for both. Conclusions: Non-gradient social class disparities related to tooth brushing were recognized for the Korean adults. The behavior of brushing teeth at two different times revealed a different pattern of social inequality regarding oral health. Thus, workplace-based oral health promotion programs should be implemented.